Local and Non-local Effects of Foam Rolling on Passive Soft Tissue Properties and Spinal Excitability - Nakamura, Masatoshi; Konrad, Andreas; Kiyono, Ryosuke; Sato, Shigeru; Yahata, Kaoru; Yoshida, Riku; Yasaka, Koki; Murakami, Yuta; Sanuki, Futaba; Wilke, Jan (Frontiers in Physiology, 2021)
In sports and clinical settings, roller massage (RM) intervention is used to acutely increase range of motion (ROM); however, the underlying mechanisms are unclear. Apart from changes in soft tissue properties (i.e., reduced passive stiffness), neurophysiological alterations such as decreased spinal excitability have been described. However, to date, no study has investigated both jointly. The purpose of this trial was to examine RM’s effects on neurophysiological markers and passive tissue properties of the plantar flexors in the treated (ROLL) and non-treated (NO-ROLL) leg. Fifteen healthy individuals (23±3 years, 8 females) performed three unilateral 60s bouts of calf RM. This procedure was repeated four times on separate days to allow independent assessments of the following outcomes without reciprocal interactions: dorsiflexion ROM, passive torque during passive dorsiflexion, the shear elastic modulus of the medial gastrocnemius muscle, and spinal excitability. Following RM intervention, dorsiflexion ROM increased in both ROLL (+19.7%) and NO-ROLL (+13.9%) legs, whereas passive torque at dorsiflexion ROM increased in both ROLL (+15.0%) and NO-ROLL (+15.2%) legs. However, there were no significant changes in shear elastic modulus and spinal excitability (p > 0.05). Moreover, significant correlations were observed between the changes in DF ROM and passive torque at DF ROM in both ROLL and NO-ROLL legs. Changes in ROM after RM appear to be the result of sensory changes (e.g., passive torque at DF ROM), affecting both rolled and non-rolled body regions. Thus, therapists and exercise professionals may consider applying remote treatments if local loading is contraindicated.